CHANGES IN TEACHERS’ REFLECTION AFTER LESSON STUDY PROCESS (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ This qualitative study explores if there were any changes in teachersâ€™ reflection in terms of content and levels after participating in five lesson study cycles.Method â€“ Case study method was employed in this study. Six mathematics teachers from a primary school participated in this study. They set up a lesson study group and conducted five lesson study cycles. In each lesson study cycle, the lesson study team members plan, teach and observe a research lesson. Qualitative data was collected through participatory observation, reflection sessions, collection of artefacts and interviews.Findings â€“ Analysis of data revealed that there were some slight and slow changes in the teachersâ€™ reflection as they progressed from the first to the fifth reflection sessions. These changes included: (1) teachersâ€™ reflection became more specific and in-depth; (2) teachersâ€™ reflection about the pupilsâ€™ learning became more in-depth; (3) teachers reflected from pupilsâ€™ perspectives; and (4) teachers reflect athigher level of reflection.Significance â€“ The study revealed that the criteria of lesson study, collaborative and classroom observation, made it feasible in promoting teachersâ€™ reflection. The educators could employ lesson study as an approach to promote teachersâ€™ reflection. However, the effectiveness of lesson study in promoting teachersâ€™ reflection is 146 Malaysian Journal of Learning and Instruction: Special Issues 2017: 145-172 affected by the number of lesson study cycles being carried out and the presence of the knowledgeable others.